If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6(x + -4) + 3x = 5(2x + 8) + -14 Reorder the terms: 6(-4 + x) + 3x = 5(2x + 8) + -14 (-4 * 6 + x * 6) + 3x = 5(2x + 8) + -14 (-24 + 6x) + 3x = 5(2x + 8) + -14 Combine like terms: 6x + 3x = 9x -24 + 9x = 5(2x + 8) + -14 Reorder the terms: -24 + 9x = 5(8 + 2x) + -14 -24 + 9x = (8 * 5 + 2x * 5) + -14 -24 + 9x = (40 + 10x) + -14 Reorder the terms: -24 + 9x = 40 + -14 + 10x Combine like terms: 40 + -14 = 26 -24 + 9x = 26 + 10x Solving -24 + 9x = 26 + 10x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-10x' to each side of the equation. -24 + 9x + -10x = 26 + 10x + -10x Combine like terms: 9x + -10x = -1x -24 + -1x = 26 + 10x + -10x Combine like terms: 10x + -10x = 0 -24 + -1x = 26 + 0 -24 + -1x = 26 Add '24' to each side of the equation. -24 + 24 + -1x = 26 + 24 Combine like terms: -24 + 24 = 0 0 + -1x = 26 + 24 -1x = 26 + 24 Combine like terms: 26 + 24 = 50 -1x = 50 Divide each side by '-1'. x = -50 Simplifying x = -50
| 9x+7=7x+37 | | 12+4q+1=5(q+5) | | c+1-3=-21 | | .05t+.012(t+1)=.57 | | -4(17y-15)=-6(4+12y) | | 2(1.43)-y=7 | | G(5n)=2x^2-5 | | (-4x)+6=(-2x)+10 | | 20g-16=8(6g+19) | | -(5x-8)-(6x-3)+4=-6(x-4)-(9x+9)+3 | | 5x+(-2)=2x+10 | | -14.18-16.6v=-16.3v-9.68 | | 2x=84-12 | | s+4=7.3 | | -2(n+1)=19+n | | 3(2x+7)=-48+63 | | 2z=-4z-2 | | 3x+30=3x+30 | | (7x-3)+(12x-7)=189 | | -x+6=2x | | 3x-(x+1)=-3+4(x-5) | | -4(x+8)=18-6(x-5) | | 4.5(2r-6)-3r= | | -4+y=-3 | | 1.6x=8.32 | | -3(x+5)=7+12(x-2) | | -4(3-3x)+7x=-37-6x | | 3x-2(7-2x)=10 | | -4=v-9 | | -3(2y-5)=7(y-2) | | 7(x-7)-4=-40-6x | | -(4x-9)-(3x-7)+6=-6(x-9)-(5x+6)+5 |